Pemberdayaan UMKM Bambu Banjarnegara melalui Edukasi dan Penerapan Konsep Value chain - prasetio, dian eko adi; lemadi, gayuh; zulkarnaen, iskandar; pratignyo, lisana sumarah (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2025)
This community service program was carried out at D’Bantar Bamboo Craft, Banjarnegara, aiming to improve the understanding and skills of bamboo SMEs in implementing an integrated value chain approach. The activity was driven by Banjarnegara’s abundant bamboo resources, which remain underutilized due to traditional business management, low production efficiency, and limited marketing strategies. The method employed a participatory approach through a Focus Group Discussion (FGD), including lectures, interactive discussions, case studies, and field mentoring. Understanding levels were measured before and after the program using a questionnaire. Results show an increase in average understanding scores from 1.71 (low) to 2.82 (moderate to high), representing a 65% improvement. Most participants shifted from low to high categories, indicating the program’s effectiveness in enhancing knowledge and awareness of value chain management. This activity contributes significantly to improving the competitiveness of bamboo SMEs and serves as a foundation for further mentoring programs.